Finance board game: critical thinking for the blind / Yufarisha Nur Rania Mohd Yuzakri … [et al.] - Mohd Yuzakri, Yufarisha Nur Rania; Zaharin, Dayang Zahirah; Wan Azhab, Wan Arisa Sofea; Mohamad Azhar, Nor Alysa Atiqa; Roslan, Nur Meelna Marlinie; Mahamad Husin, Nur Adnin; Awang, Amizatul Hawariah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Monopoly is a board game where players will be playing their role as realtors. The purpose is to be financially stable by purchasing properties while on the other hand forcing opponents into bankruptcy. This edition is also the same but with additional attributes. It is for people who are blind or visually impaired. We offer them the feeling of enjoyment just like other human beings. Moreover, they can also enhance learning. This version adds technology as the special trait which makes playing convenient for them. For your information, Monopoly: Special Care Edition takes inspiration from the movie Jumanji.